Photonic Generation and Application of a Bandwidth Multiplied Linearly Chirped Signal With Phase Modulation Capability - Xuan Li (IEEE Access, 2021)
Photonic generation of a bandwidth multiplied linearly chirped signal with phase modulation capability is proposed and its applications in communication and radar systems are demonstrated. In the generator, a dual-polarization quadrature phase shift keying modulator is used to simultaneously perform bandwidth multiplication and phase modulation. The generator can be functionally expanded to a transceiver for wireless communication, which can be used to perform optical generation and coherent demodulation of a phase modulated linearly chirped signal. Meanwhile, the generator can be used to increase the radar detection distance by improving the signal time bandwidth product. The signal generation and application are verified by simulation. A linearly chirped signal with an instantaneous frequency of 8–12 GHz or 16–24 GHz is obtained by using a 4–6 GHz electrical driving signal. The proposed transceiver is demonstrated to perform 156.25-bit/s wireless communication. When the emitting power is 11 dBm and the communication distance is 1 km, the bit error rate can be better than 10−4. While for radar detection, the peak to sidelobe ratio of the compressed pulse is increased from 1.1 dB to 9.2 dB, through which the distance improvement can be verified.